THE IMPORTANCE OF ECOLOGICAL MARKETING IN THE DEVELOPMENT OF PRODUCTION BASED ON GREEN TECHNOLOGIES (Marketing Journal, 2025)
This article analyzes the role of ecological marketing in developing production based on green technologies. The focus is on identifying the link between ecological values, digital communication tools, and production efficiency. Based on the literature review, ecological marketing is shown to enhance brand trust, promote green employment, and support sustainable economic models. Practical recommendations are developed through conceptual and comparative analysis.
Keywords: ecological marketing; green technologies; sustainable production; digital communication; consumer trust